Analisis Rekruitmen Karang pada Terumbu Buatan di Perairan Desa Bondalem, Kecamatan Tejakula, Kabupaten Buleleng, Bali - Prasetya, Putu Angelina; Wiyanto, Dwi Budi; Sila Dharma, I Gusti Bagus (Journal of Marine Research and Technology; Vol 7 No 2 (2024): OKTOBER 2024, 2024)
Coral reef rehabilitation is one of recovery a damaged coral reef ecosystem. One of the coral reef rehabilitation that has been carried out was the deployment of artificial reefs on the Indonesia Coral Reef Garden (ICRG) project in Bondalem Village on 2020. However, there is no data yet that indicates the program success. Therefore, this study aimed to determine the physical and chemical conditions of the waters, the structure of the coral community, composition and abundance of recruited corals, and the effect of sedimentation rates on coral abundance on artificial reefs. The methods used in this study were visual census and photography, by observing the appearance of corals from images, which were then identified to genus level. The data analysis used includes indices of diversity, evenness, dominance, and abundance, as well as linear regression analysis to determine the effect of sedimentation rates on coral recruits. The physical and chemical conditions of the waters at the observation site are still considered normal. A total of 23 coral genera were found, with the highest number of colonies coming from the genera Pocillopora and Acropora. The highest diversity was found at Station 2 with value 2.67-3.25. The highest evenness (E) was found at Station 1 with value 0.75-0.76. The highest dominance (C) was found at Station 3 with value 0.40-0.53. The results showed that the sedimentation rate had a 68% correlation with the abundance of coral recruits, that indicated the sedimentation rate had negatively affected of the abundance of coral recruits.